Identification and characterization of promising endophytic bacteria for growth promotion in chickpea (Cicer arietinum) - Batra, Priyanka; Barkodia, Monika; Ahlawat, Umang; Sansanwal, Rekha; Vaid, Rajesh Kumar; Wati, Leela (The Indian Journal of Agricultural Sciences, 2020)
The present study was carried out for the isolation and characterization of endophytic bacteria from chickpea nodules. A total of 107 endophytes were isolated from five districts of Haryana using three media, viz. YEMA for rhizobia, Pikovskaya and TSA for non-rhizobial isolates. The endophytes were then screened for various growth promoting traits like IAA production, Phosphate solubilization, Siderophore production, ACC utilization, Potassium solubilization and tolerance to NaCl concentrations. Total six endophytes, one rhizobium (HM2) and five non-rhizobial endophytes (RE6, BE13, ME3, HE5, HE7) were selected based on of plant growth promoting traits. Furthermore, the most promising non-rhizobial endophytes RE6 and BE13, compatible with Rhizobial isolate HM2 were Pseudomonas protegens and Bacillus boroniphilus using 16s rDNA sequencing. Both the isolates are non-pathogenic to humans and thus, are potential plant probiotics that can be used as biofertilizers.